The burden of tuberculosis and drug resistance in 22 Sub-Saharan African countries, 1990–2021: a GBD 2021 analysis and progress towards WHO 2035 targets with projections to 2050 - Li, Shirong; Mensah, Emmanuel; Liu, Min; Pan, Lingling; Lu, Wei; Zhou, Susheng; Zhang, Liqin; Cheng, Yusheng; Zhao, Hui; Wei, Shuoshuo; Zha, Lei (Frontiers in Microbiology, 2025)
BackgroundTuberculosis (TB) remains a major public health challenge in Sub-Saharan Africa (SSA), compounded by rising multidrug-resistant (MDR-TB), and extensively drug-resistant tuberculosis (XDR-TB) strains. This study aimed to quantify the burden, temporal trends, and subregional heterogeneity of TB across 22 selected SSA countries; project future trends to 2050; and evaluate the alignment of national TB policies with WHO End TB 2035 targets.MethodsWe conducted a mixed-methods analysis using Global Burden of Disease (GBD) 2021 data. Age- and sex-specific TB incidence, prevalence, mortality, and disability-adjusted life years (DALYs) were analyzed across 22 SSA countries from 1990 to 2021. BAPC model projected disease burden to 2050. National TB policy alignment with WHO targets was assessed qualitatively. Drug-susceptible (DS-TB), MDR-TB, and XDR-TB forms were evaluated alongside key attributable risk factors.ResultsBetween 1990 and 2021, absolute TB incidence in SSA increased by 25.6% and prevalence by 44.2%, while mortality and DALYs declined by 14.0 and 24.8%, respectively. Age-standardized rates declined significantly across all metrics; incidence (−46.2%), prevalence (−35.2%), mortality (−56.4%), and DALYs (−60.9%). Progress varied substantially by region: Western SSA showed the greatest improvement, while Southern and Central SSA continued to face high burdens, with rising mortality in some areas. MDR-TB incidence surged by 743.2%, with XDR-TB also increasing markedly, particularly in Eastern and Central SSA. HIV co-infection amplified MDR/XDR-TB mortality, with Southern SSA most affected. Age- and sex-specific analyses revealed early-adulthood incidence peaks, male predominance in mortality and DALYs, and the highest MDR-TB burden among older adults. Leading risk factors for TB mortality included high alcohol use, elevated fasting plasma glucose, tobacco use, and high body mass index. Projections indicate SSA is unlikely to meet the WHO 2035 mortality reduction target, though Ghana, Guinea, and Tanzania are projected to achieve the incidence target.ConclusionDespite overall declines in TB mortality, the growing DR-TB/MDR-TB/XDR-TB epidemic, significant subregional disparities, and systemic health system challenges threaten progress toward WHO End TB goals. Strengthening diagnostics, expanding treatment access, integrating care services, and addressing key metabolic and behavioral risk factors are essential to accelerate TB control efforts and align SSA with the 2035 targets.